2022
DOI: 10.1002/wps.20941
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of psychotherapies and pharmacotherapies for mental disorders in adults: an umbrella review and meta‐analytic evaluation of recent meta‐analyses

Abstract: Mental disorders represent a worldwide public health concern. Psychotherapies and pharmacotherapies are recommended as first line treatments. However, evidence has emerged that their efficacy may be overestimated, due to a variety of shortcomings in clinical trials (e.g., publication bias, weak control conditions such as waiting list). We performed an umbrella review of recent meta‐analyses of randomized controlled trials (RCTs) of psychotherapies and pharmacotherapies for the main mental disorders in adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
161
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(179 citation statements)
references
References 177 publications
(369 reference statements)
6
161
0
12
Order By: Relevance
“…However, a sensitivity analysis excluding these studies showed no significant difference. Seventh, based on the evidence from a recent study in adults [ 46 ], the effects of antidepressants on functioning and QOL in children and adolescents with MDD might be also overestimated due to potential observers’ bias of functioning and QOL outcomes in our included trials, which would be an interesting topic in further study. Finally, to reduce heterogeneity across studies, we excluded patients with treatment-resistant depression, which may have led to an overestimation of effects because of the omission of a difficult-to-treat population.…”
Section: Discussionmentioning
confidence: 99%
“…However, a sensitivity analysis excluding these studies showed no significant difference. Seventh, based on the evidence from a recent study in adults [ 46 ], the effects of antidepressants on functioning and QOL in children and adolescents with MDD might be also overestimated due to potential observers’ bias of functioning and QOL outcomes in our included trials, which would be an interesting topic in further study. Finally, to reduce heterogeneity across studies, we excluded patients with treatment-resistant depression, which may have led to an overestimation of effects because of the omission of a difficult-to-treat population.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological interventions for adult PTSD appear more effective than psychological interventions more generally, that is, across mental disorders. A recent umbrella review and meta-analysis 80 summarized findings of 3,782 RCTs (N = 650,514 patients) on the efficacy of psychological interventions and pharmacotherapies for the treatment of various mental disorders and found a pooled SMD of 0.34 (95% CI: 0.26-0.42) for psychological interventions as monotherapy compared to placebo or treatment-as-usual, which is substantially below the SMDs found for psychological interventions in the present NMA (e.g., SMD of TF-CBT vs active control conditions at post-treatment assessment = 0.60).Similar results have been reported elsewhere. For instance, psychological interventions for PTSD produce larger treatment effects than psychological interventions for other anxiety-related disorders 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Empirically Supported Treatments (EST) movement has helped clinical psychologists to reach an agreement on the efficacy of psychological treatments for specific problems (Nathan & Gorman, 2015). However, after all the resources invested in clinical research, the effect sizes of psychological interventions are limited and researchers are starting to suggest a ceiling effect for clinical research as presently conducted (Leichsenring et al, 2022). Probably these results are generated by pervasive problems in clinical research psychology as the undying influence of the latent disease model of psychiatry, manualized treatment for specific diagnostic labels, and the separation between therapeutic processes and clinical outcomes (Hofmann & Hayes, 2019;Tolin et al, 2015).…”
Section: Functional Coding System To Analyze Verbal Interaction In Cl...mentioning
confidence: 99%